Third-generation electrochemical biosensor based on nitric oxide reductase immobilized in a multiwalled carbon nanotubes/1-n-butyl-3-methylimidazolium tetrafluoroborate nanocomposite for nitric oxide detection - Gomes, Filipa O. (2019)
Nitric oxide (NO) has a crucial role in signaling and cellular physiology in humans. Herein, a novel third-generation biosensor based on the Marinobacter hydrocarbonoclasticus metalloenzyme (nitric oxide reductase (NOR)), responsible for the NO reduction in the denitrifying processes, was developed through the direct adsorption of a new nanocomposite (multiwalled carbon nanotubes (MWCNTs)/1-n-butyl-3-methylimidazolium tetrafluoroborate (BMIMBF4)/NOR) onto a pyrolytic graphite electrode (PGE) surface. The NOR direct electron transfer behavior (formal potential of -0.255 ± 0.003 V vs. Ag/AgCl) and electrocatalysis towards NO reduction (−0.68 ± 0.03 V vs. Ag/AgCl) of the PGE/[MWCNTs/BMIMBF4/NOR] biosensor were investigated in phosphate buffer at pH 6.0. Large enzyme loading (2.04 × 10−10 mol/cm2), acceptable electron transfer rate between NOR and the PGE surface (ks = 0.35 s-1), and high affinity for NO (Km = 2.17 μmol L-1) were observed with this biosensor composition. A linear response to NO concentration (0.23–4.76 μmol L-1) was perceived with high sensitivity (0.429 μA/μmolL-1), a detection limit of 0.07 μmol L-1, appropriate repeatability (9.1% relative standard deviations (RSD)), reproducibility (6.0–11% RSD) and 80–102% recoveries. The biosensor was stable during 1 month retaining 79–116% of its initial response. These data confirmed that NOR incorporated in the MWCNTs/BMIMBF4 nanocomposite can efficiently maintain its bioactivity paving a new and effective way for NO biosensing.